Turbulence regimes and the validity of similarity theory in the stable boundary layer over complex terrain of the Loess Plateau, China. Issue 10 (29th May 2014) - Liang, Jiening; Zhang, Lei; Wang, Ying; Cao, Xianjie; Zhang, Qiang; Wang, Hongbin; Zhang, Beidou
Abstract To gain an insight into the characteristics of turbulence in a stable boundary layer over the complex terrain of the Loess Plateau, data from the Semi‐Arid Climate and Environment Observatory of Lanzhou University are analyzed. We propose a method to identify and efficiently isolate nonstationary motions from turbulence series, and then we examine the characteristics of nonstationary motions (nonstationary motions refer to gusty events on a greater scale than local shear‐generated turbulence). The occurrence frequency of nonstationary motions is found to depend on the mean flow, being more frequent in weak wind conditions and vanishing when the wind speed, U, is greater than 3.0 m s−1. When U exceeds the threshold value of 1.0 m s−1 for the gradient Richardson number Ri ≤ 0.3 and 1.5 m s−1 for Ri > 0.3, local shear‐generated turbulence on timescales of less than 4 min depends systematically on U with an average rate of 0.05 U. However, for the weak wind condition, neither the mean wind speed nor the stability is an important factor for local turbulence. Then turbulence is categorized into three regimes based on the behaviors of nonstationary motions and local turbulence. Regime 1 considers stationary turbulence with a wind speed greater than 3.0 m s−1, and the Monin‐Obukhov similarity theory (MOST) can be used to calculate the turbulence momentum flux. Regime 2 examines intermittent turbulence where the MOST is competent to evaluate the local turbulence momentum flux but not nonstationary motions. Regime 3 involves wind speed that is less than the threshold value, where nonstationary motions are dominant, local turbulence is independent of the mean flow, and where the MOST may well be invalid.